Identifikasi Sistem Perencanaan Strategi Pengelolaan Kinerja Berbasis Balance Scorecard - Kristianus Hiktaop; Wayrohi Meilvidiri (Universitas Musamus,Merauke,Papua, 2021)
The concept of the balance scorecard the pushed to be applied to public organizations as a performance measure that is considered capable of being an effective evaluation tool to improve services, in 2011 the Ministry of Finance has started to implement the BSC, and it has enabled the ministry to transform into an institution with the best public service quality, It is hoped that this success can also be followed by other government agencies and this is also a reference for this paper where the objectives is to identify a comprehensive public performance strategy planning system based on the Balance scorecard in the Regional Revenue Agency of Merauke Regency. The research paradigm used is a descriptive qualitative approach, using primary data obtained through observation, questionnaire forms, interviews, and discussions. The results of the analysis and evaluation of the balance scorecard component show that the Merauke Regency Regional Revenue agency conceptually considers the strategic planning system of the organization and personnel performance through the balance scorecard approach, however, in the future Bapenda is expected to be able to fully implement the Balance Scorecard as a governance model that is not only planned but implemented.